Research of the Test Method of Double Stress Step-down Acceleration Life for Harmonic Reducer - Jing Wang; Menglun Tao; Dingfang Chen; Can Wu; Junfeng Wu; Fang Chen; Bo Li (Jixie chuandong)
Aiming at the problems of low efficiency and imperfect test scheme of the existing accelerated life test of the harmonic reducer， a double stress step-down accelerated life test method is proposed. Taking the harmonic reducer for industrial robots as the research object， through comparing the acceleration schemes and analyzing the failure mechanism of accelerated life， a double stress step-down test load spectrum is formulated. Based on the iterative relationship between the step-down load stresses of each segment， the optimal parameters of Weibull distribution of harmonic driver are calculated by genetic algorithm. The results show that the acceleration factor for this double stress step-down life test is 12.5. The test efficiency is accurately and effectively improved by this scheme， and a reference for optimizing the design of the harmonic reducer and shortening the test cycle of the accelerated life test of the harmonic reducer are provided.